2005
DOI: 10.1080/08910600500430664
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the gut flora of Irish breastfed and formula-fed neonates aged between birth and 6 weeks old

Abstract: Comparing the gut flora of Irish breastfed and formula-fed neonates aged between birth and 6 weeks old. Microbial Ecology in Health and DiseaseJan 2005, Vol. 17, No. 3, Pages 163-168 (doi:10.1080/ 08910600500430664) Microbiological methods were used to specifically enumerate Lactobacilli sp., Bifidobacteria sp., Enterococci sp., Staphylococci sp., Bacteroides sp., Clostridia sp. and coliforms present in the gut. The data indicated major trends present, including the fact that Bifidobacteria sp. and Lacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(6 reference statements)
0
9
0
Order By: Relevance
“…Specifically, formula feeding has been associated with increased bacterial diversity [91], increased prevalence of C. difficile [79], Bacteroides fragilis , and E. coli [79,92], and decreased prevalence of bifidobacteria [93]. Formula, even given in small amounts during breastfeeding, can alter the structure [94] and relative abundances [69] of the bacterial communities normally found in a breastfed infant gut.…”
Section: Disruptors Of the Colonization And Development Of The Neonatmentioning
confidence: 99%
“…Specifically, formula feeding has been associated with increased bacterial diversity [91], increased prevalence of C. difficile [79], Bacteroides fragilis , and E. coli [79,92], and decreased prevalence of bifidobacteria [93]. Formula, even given in small amounts during breastfeeding, can alter the structure [94] and relative abundances [69] of the bacterial communities normally found in a breastfed infant gut.…”
Section: Disruptors Of the Colonization And Development Of The Neonatmentioning
confidence: 99%
“…It is often stated that breastfeeding has a profound influence on the gut microbiota, but many studies from the 1980s and onwards report only minor differences in the colonization pattern of breast-and formula-fed infants (table 2). Bifidobacteria are mostly found equally often and in similar counts in breast-and formula-fed infants using conventional culture- [2,9,21,23,40,[63][64][65][66] or non-culture-dependent methods [15,[67][68][69][70][71]. Previous reports of marked differences in the colonization frequency of bifidobacteria between breast-and formula-fed infants may be explained by the use of older types of infant formulas with higher protein and phosphate content.…”
Section: Breastfeeding and Intestinal Colonization Patternmentioning
confidence: 99%
“…This previously unreported identification of the strains E. agglomerans, S. marcescens and E. faecium as menaquinone producers will in the first instance contribute to aiding in their microbiological classification (11). In addition, the sourcing of these additional vitamin K-producing strains from the neonatal gut flora shows their potential as bacteria that could contribute in the neonate to the overall requirements of vitamin K, an essential vitamin in the human blood clotting process (6). In the study presented here, the newly identified vitamin Kproducing strains together with the several other previously reported vitamin K-producing strains identified in this study namely, Bacteroides ovatus, Citrobacter freundii, Enterococcus faecalis, Escherichia coli, Prevotella buccae, Staphylococcus capitis, Staphylococcus epidermidis, Staphylococcus haemolyticus and Staphylococcus warneri, were predominantly isolated only in the 6-week-old faecal samples rather than in the 0 Á1or 2Á5-day-old samples analysed (unpublished results).…”
Section: Discussionmentioning
confidence: 92%